Doxorubicin Activity Is Modulated by Traditional Herbal Extracts in a 2D and 3D Multicellular Sphere Model of Leukemia - Laura Corzo Prada; Claudia Urueña; Efraín Leal-García; Alfonso Barreto; Ricardo Ballesteros-Ramírez; Viviana Rodríguez-Pardo; Susana Fiorentino (MDPI AG, 2023)
The modulation of the tumor microenvironment by natural products may play a significant role in the response of tumor cells to chemotherapy. In this study, we evaluated the effect of extracts derived from P2Et (Caesalpinia spinosa) and Anamú-SC (Petiveria alliacea) plants, previously studied by our group, on the viability and ROS levels in the K562 cell line (Pgp− and Pgp+), endothelial cells (ECs, Eahy.926 cell line) and mesenchymal stem cells (MSC) cultured in 2D and 3D. The results show that: (a) the two botanical extracts are selective on tumor cells compared to doxorubicin (DX), (b) cytotoxicity is independent of the modulation of intracellular ROS for plant extracts, unlike DX, (c) the interaction with DX can be influenced by chemical complexity and the expression of Pgp, (d) the 3D culture shows a greater sensitivity of the tumor cells to chemotherapy, in co-treatment with the extracts. In conclusion, the effect of the extracts on the viability of leukemia cells was modified in multicellular spheroids with MSC and EC, suggesting that the in vitro evaluation of these interactions can contribute to the comprehension of the pharmacodynamics of the botanical drugs.